Radio-Telemetry in Biomedical Research - Radio-Telemetry Blood Pressure Measurements in Animal Models of Hypertension, How It Revolutionized Hypertension Research - Dumas, Pierre; Chiche, Dan; Tremblay, Johanne; Šeda, Ondřej; Peng, Junzheng; Hamet, Pavel (IntechOpen, 2011)
None